2017
DOI: 10.1111/1462-2920.13916
|View full text |Cite
|
Sign up to set email alerts
|

The diversity and biogeography of abundant and rare intertidal marine microeukaryotes explained by environment and dispersal limitation

Abstract: SummaryBenthic microeukaryotes are key ecosystem drivers in marine sandy beaches, an important and dynamic environment; however, little is known about their diversity and biogeography on a large spatial scale. Here, we investigated the community composition and geographical distributions of benthic microeukaryotes using high-throughput sequencing of the 18S rRNA gene and quantified the contributions of environmental factors and spatial separation on the distribution patterns of both rare and abundant taxa. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
84
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 73 publications
11
84
4
2
Order By: Relevance
“…Consistent with our present study, some recent studies revealed that abundant and rare bacterioplankton in freshwater lakes and reservoirs were also significantly correlated with different environmental factors [31,35]. Interestingly, similar observations have also been reported in activated sludge bioreactor [30], soil [50], and intertidal marine ecosystem [72]. Recent work has confirmed that abundant and rare bacterial taxa had discrepant ecological niches and different roles in oil-contaminated soils [50].…”
Section: Linking Environmental Factors With Bacterioplankton Communitsupporting
confidence: 92%
“…Consistent with our present study, some recent studies revealed that abundant and rare bacterioplankton in freshwater lakes and reservoirs were also significantly correlated with different environmental factors [31,35]. Interestingly, similar observations have also been reported in activated sludge bioreactor [30], soil [50], and intertidal marine ecosystem [72]. Recent work has confirmed that abundant and rare bacterial taxa had discrepant ecological niches and different roles in oil-contaminated soils [50].…”
Section: Linking Environmental Factors With Bacterioplankton Communitsupporting
confidence: 92%
“…They are an important part of marine food webs, supplying organic carbon to higher trophic levels in both plankton and benthos, and are an important component of the vertical flux of organic carbon in the sea (Tirichine et al ). A previous study demonstrated that diatoms are the dominating group (by sequence number) among the 43 deep‐branching lineages of microeukaryotes (Zhang et al ), indicating their important role in ecosystems. In total, 439 Bacillariophyta OTUs were detected in this study which was higher than previous work focusing on diatoms in intertidal sediments that was based on microscopy and/or PCR‐DGGE methods (Sahan et al ; Ribeiro et al ; Siqueiros‐Beltrones et al ).…”
Section: Discussionmentioning
confidence: 99%
“…This study provides the first detailed insights into the diversity and biogeography of Cercozoa in intertidal sandy ecosystems. In total, 661 Cercozoa OTUs were recovered, comprising 5.1% of the total microeukaryote OTUs (Zhang et al ). A previous study found that Cercozoa comprised between 9% and 24% of all assigned eukaryotic OTUs on the ocean floor of the Arctic and Southern Oceans (Pawlowski et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations